The Potential of Clove (Syzygium aromaticum) Essential Oil as Sunscreen and Anti-Aging Agents: An In Vitro and In Silico Study - Husen, Rifsia Ajani; Zulkarnain, Zulkarnain; Sary, Nirwana Lazuardi; Harnelly, Essy; Husna, Fauzul (Trends in Sciences, 2024)
The earth thermal conditions increase exposure to sunlight, triggering skin damage. The skin has defense mechanisms but needs additional protection to prevent photoaging. Using sunscreen is an effort to reduce the harmful effects of sun exposure. Natural ingredients with antioxidant activity can be developed into sunscreen and antiaging products, including cloves. This study aims to assess the antioxidant, sun protection, and anti-aging properties of essential oils derived from clove leaves and buds. The antioxidant activity was assessed by the DPPH system and then formulated into 5 and 10 % clove leaves cream, as well as 5 and 10 % clove bud cream. The SPF values were assessed using a spectrophotometer and the Mansur formula. The antiaging potential was assessed using the in silico method with MMP-1 protein employing the Auto Dock Vina software, followed by analysis and visualization using BIOVIA Discovery Studio. The essential oils from clove leaves and buds have DPPH IC50 values of 23.09 and 30.31 ppm. The SPF values of clove leaves essential oil, 5 % leaves cream, and 10 % leaves cream are 38.61, 14.32, and 22.15. Meanwhile, the SPF values of clove bud essential oil, 5 % bud cream, and 10 % bud cream are 38.19, 9.32, and 18.16. The in silico test revealed that caryophyllene, eugenol, humulene, and phenol, 2-methoxy-4-(2-propenyl), acetate) have strong interactions because they can interact with the active site of proteins using hydrogen, hydrophobic, and van der Waals bonds. The essential oils from clove leaves and buds exhibit very strong antioxidant activity and offer ultra-protection as a sunscreen. The cream formulations still exhibit sunscreen activity, albeit at a lower level compared to pure essential oil. Caryophyllene, eugenol, humulene, and phenol, 2-methoxy-4-(2-propenyl)-, acetate), have potential as antiaging agents, as indicated by their binding affinity and chemical bond interactions observed in the in silico test. HIGHLIGHTS Clove buds and leaves exhibit antioxidant properties. Essential oil from clove buds and leaves demonstrates a substantial Sun Protection Factor (SPF). The compounds contained in clove essential oil exhibit promise as prospective agents in anti-aging applications. GRAPHICAL ABSTRACT